202 NUMARALI MANİSA ŞER'İYYE SİCİLİ (H.1149-1150-1151/M.1736-1737-1738) - SERTEL, UĞUR (Fırat Üniveristesi, 2004)
Tezimin birinci bölümünde Osmanlı Devleti 'nde Adalet Teşkilatı ve Şerciyye Sicilleri hakkında bilgi verdim. Ayrıca bu bölümde Osmanlı Devleti'nde Kadılık Kurumu, Mahkeme ve Mahkeme Görevlileri ve Şerciyye Sicilleri 'nin muhtevalarını inceledim. Tezimin ikinci bölümünde 202 Numaralı Manisa Şerciyye Sicili'nde yer alan belgelerin konularına göre tasnifini yaptım. Sonra sonuç, bibliyografya ve ekleri koyarak tezimi tamamladım. Anahtar Kelimeler: Kadı, Sicil, Mahkeme, Belge.

In the first chapter of my thesis, I gave education about justice constitutions and şerciyye registers in the Otoman Empire. In addition inthis chapter I investigated Kadılık Society, court and the employers of court, Cadi and the Cadi's duties and Şerciyye sregisters contents in the Otoman Empire. In the secord chapter of my thesis I made the arranging of the documents which are existingin the numbered 202 of Manisa Şerciyye register. Then I made the Summarize of documents, text's transciription. In the end, I finished my thesis with putting, bibliography and joints. Key words: Cadi, register, court, document.
Numbered 202 Manisa Şer'iyye sicili (H.1149-1150-1151/M.1736-1737-1738)
Keywords: Tarih; History